Interchangeability and maintainability of electric vehicles in the context of industry development - Gorbenko, O.; Lazorenko, A.; Горбенко, Олександр Вікторович; Лазоренко, Андрій Ігорович (Харківський національний автомобільно-дорожній університет, 2025)
The rapid growth of the global electric vehicle (EV) market is accompanied by a low level of interchangeability and maintainability of key components, leading to increased maintenance costs, dependence on authorized service centers, and challenges in battery recycling. The absence of unified design standards limits the possibilities for component reuse and creates technical barriers to the development of an efficient service infrastructure. Goal. To analyze the current state of interchangeability and maintainability of electric vehicles, identify technical, economic, and regulatory constraints, and develop recommendations for standardization and unification of design solutions aimed at improving the economic and environmental efficiency of EV operation. Methodology. The study employs a comparative analysis of EV designs from different manufacturers, a review of international standards (ISO 15118, CCS Combo, IEC 61851, SAE J1772), and systematization of service-related barriers. Economic risks associated with full-unit replacement and environmental consequences of limited battery recycling were assessed. Serviceability challenges and critical cost factors were analyzed using TCO (Total Cost of Ownership) indicators. Results. It has been revealed that most EV components have unique design parameters, preventing the use of universal spare parts and increasing TCO by 20–40%. A set of technical, economic, and regulatory measures is proposed, including modular architecture, dimensional interface unification, and the implementation of open diagnostic protocols. These solutions are expected to improve service accessibility and reduce vehicle downtime. Originality. Unlike existing studies, this paper integrates technical, economic, and serviceability aspects by proposing a structured scheme for standardizing EV components at technological, service, and environmental levels. A novel approach to evaluating maintainability is offered through indicators of modularity, compatibility, and availability of certified spare parts. Practical value. The findings can be used for the development of regulatory frameworks in the field of electric transport, the design of modular battery and power electronics systems, the creation of a market for certified component analogs, and the implementation of battery reuse programs. The proposed solutions contribute to reducing maintenance costs, extending vehicle lifespan, and minimizing environmental impact.
Взаємозамінність та ремонтопридатність електротранспорту в контексті розвитку галузі
Keywords: electric vehicle; interchangeability; maintainability; standardization; maintenance; unification; service infrastructure; ремонтопридатність; стандартизація; обслуговування; уніфікація; сервісна інфраструктура.; 629.331.073:629.33-592:621.3.078; 10.30977/AT.2219-8342.2025.57.0.09